Respostas

2013-11-05T23:34:28-02:00
X + 5y = - 24
x = - 24 - 5y

3x - 2y = - 4
- 2y = - 4 - 3x ( - 1)
y = 4 + 3x / 2

y = 4 + 3( - 24 - 5y) / 2
y = 4 - 72 - 15y / 2
2y = - 15y - 68
17y = - 68                                                                                                             
                              y =  - 4

x = - 24 - 5 . (-4)
x = - 24 + 20
                                x = - 4
1 5 1
2013-11-06T02:44:17-02:00
X = -5y - 24 ai substitui na otra equacao
3•-5y -24 = -4
17y:-68
Y:-4
X:-4